Separate physical tests of lower extremities and postural control are associated with cognitive impairment. Results from the general population study Good Aging in Skåne (GÅS-SNAC) - Bramell-Risberg E (Dove Medical Press, 2012)
Eva Bramell-Risberg,1 Gun-Britt Jarnlo,2 Sölve Elmståhl11Division of Geriatric Medicine, 2Division of Physiotherapy, Department of Health Sciences, Lund University, Lund, SwedenPurpose: To investigate whether separate physical tests of the lower extremities, that assess movement speed and postural control, were associated with cognitive impairment in older community-dwelling subjects.Subjects and methods: In this population-based, cross-sectional, cohort study, the following items were assessed: walking speed, walking 2 × 15 m, Timed Up and Go (TUG) at self-selected and fast speeds, one-leg standing, and performance in step- and five chair-stand tests. The study comprised 2115 subjects, aged 60–93 years, with values adjusted for demographics, health-related factors, and comorbidity. Global cognitive function was assessed using the Mini-Mental State Examination (MMSE), and cognitive impairment was defined by the three-word delayed recall task of the MMSE. Subjects who scored 0/3 on the three-word delayed recall task were defined as cases (n = 328), those who scored 1/3 were defined as intermediates (n = 457), and the others as controls (n = 1330).Results: Physical tests performed rapidly were significantly associated with cognitive impairment; this was the case in increased time of five chair stands (P = 0.009, odds ratio [OR] = 1.03), TUG (P < 0.001, OR = 1.11) and walking 2 × 15 m (P < 0.001, OR = 1.05). Inability to stand on one leg for 10 seconds was associated with increased risk of being a case (P < 0.001, OR = 1.78), compared to those able to stand for 30 seconds or longer. More steps during the step test (P < 0.001, OR = 0.95) and higher fast walking speed (P < 0.001, OR = 0.51) were associated with lower risk of being a case.Conclusion: Slower movements and reduced postural control were related to an increased risk of being cognitively impaired. All tests that were performed rapidly were able to separate cases from controls. These findings suggest that physical tests that are related to lower extremity and postural control, emphasizing velocity, might be useful in investigating relationships between physical and cognitive function; furthermore, they can be used to complement cognitive impairment diagnoses.Keywords: cognition, movement speed, TUG, walking